AOS stands for "axis of symmetry," which is a vertical line that divides a parabola into two symmetric halves.
To find the axis of symmetry of the quadratic function y = (x-3)(x+3), we can use the formula:
AOS = -b/2a
where a is the coefficient of the x^2 term, b is the coefficient of the x term, and c is the constant term.
In this case, the quadratic function is y = x^2 - 9, so a = 1 and b = 0.
Therefore, the axis of symmetry is:
AOS = -b/2a = -0/(2*1) = 0
So, the axis of symmetry for the function y = (x-3)(x+3) is the vertical line x = 0.